PAI Teachers' Perceptions of Humanist Literacy - Khairina; Nazwa Afiva; Zaidan Aimar Khadafi; Raihan Albani Dalimunthe; Mahariah (Yayasan Zia Salsabila, 2023)
The perception of humanist literacy is an individual's or society's understanding of concepts that focus on human aspects, such as tolerance, empathy, justice and human rights. Humanist literacy perceptions can help individuals or communities to understand and respond to social and humanitarian issues in a wiser way and encourage them to participate in life. This paper aims to analyze the perceptions of PAI teachers about humanist literacy. This study uses a qualitative approach with field research methods to uncover and collect research data through interview techniques and document studies. Through this research, results were found, namely teachers considered that with humanist literacy they could understand and appreciate cultural diversity, outlooks on life, and have the ability to think critically and reflectively on humanitarian and social issues.